Hydrophobically modified poly(acrylic acid) using 3-pentadecylcyclohexylamine: synthesis and rheology - Shedge, A. S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique; Pcrrin, P.; Chassenieux, Christophe; Badiger, Manohar V. (Macromolecular Chemistry and Physics, 2005)
Hydrophobically modified poly(acrylic acid) was synthesized using 3-pentadecylcyclohexylamine (3-PDCA), which was in turn synthesized from 3-pentadecylphenol, one of the components of cashew-nut shell liquid (CNSL), a renewable resource material. H-1 NMR spectra confirmed the incorporation of 3-PDCA onto PAA and a series of HMPs with three different molar concentrations, viz. congruent to 3, 5 and 7 mol-% of 3-PDCA, were synthesized. An increase in viscosity with increasing hydrophobic content was observed by rheological measurements. The critical association concentrations were determined using an Ubbelohde viscometer and a controlled stress rheometer. The stability of HMPs towards temperature and shear was studied. Rheological measurements showed that there was a steady increase in viscosity with increase in hydrophobe content due to the formation of reversible networks. These polymers exhibited gel-like behavior at low concentrations (greater than or equal to2 wt.-%) with an apparent yield stress (ca. 10 Pa) and showed shear thinning properties (non-Newtonian). However, below a critical concentration, c [eta], they showed Newtonian behavior.
Keywords: 3-pentadecylcyclohexylamine (3-PDCA); hydrophobically modified polymers (HMPs); poly(acrylic acid); reversible associations; Rheology